Estimation of dimensional criticality for direct to indirect exciton transition in a double Quantum Well: Through exciton diamagnetism. (December 2019) - Vignesh, G.; Nithiananthi, P.
Highlights: Diamagnetic Susceptibility of Direct and Indirect Excitons in Double Quantum Well is numerically calculated. The critical dimensions are evaluated for Direct to Indirect Exciton conversion. The intricate role of phonons in the formation of Excitons accounted through size dependent dielectric screening effects. Abstract: Exciton diamagnetism is calculated to estimate theoretically the critical well dimension for the transition of direct exciton (DX) to indirect (IDX) in a GaAs/Al0.3 Ga0.7 As symmetric Double Quantum Well (DQW) by variation ansatz. By tuning the confinement layer widths, the critical well size at which the constituent carriers of DX breaks up and transforms to indirect is observed through the sudden decrease of diamagnetic susceptibility (χDia ) of DX. The structural influence on the binding of DX and IDX with (i) light hole (LH) and (ii) heavy hole (HH) has been numerically estimated in the present work. The intricate role of LO phonons in the formation of exciton is accounted through the size-dependent dielectric screening.